2016
DOI: 10.1503/cjs.013115
|View full text |Cite
|
Sign up to set email alerts
|

A Canadian population-based description of the indications for lower-extremity amputations and outcomes

Abstract: Background: To our knowledge, there have been no previously published reports characterizing lower-extremity amputations in Canada. The objective of this study was to describe the indications and outcomes of lower-extremity amputations in the Canadian population. Methods:We performed a retrospective cohort study of all adult patients who underwent lower-extremity amputation in Canada between 2006 and 2009. Patients were identified from the Canadian Institute for Health Information's Discharge Abstract Database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
43
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 22 publications
7
43
1
5
Order By: Relevance
“…Schofield et al concluded that diabetic amputees have a greater risk of heart failure (OR: 2.26; 95% CI 1.12–4.57) further amputation and death than nondiabetic amputees [12] and highlighted the need for a more aggressive approach in the management of cardiovascular risk factors in those who undergo amputation and have diabetes. A recent study in the Canadian population reported that predictors of prolonged hospital stay included cardiovascular risk factors, such as diabetes, hypertension, ischemic heart disease, congestive heart failure or hyperlipidemia [42]. …”
Section: Discussionmentioning
confidence: 99%
“…Schofield et al concluded that diabetic amputees have a greater risk of heart failure (OR: 2.26; 95% CI 1.12–4.57) further amputation and death than nondiabetic amputees [12] and highlighted the need for a more aggressive approach in the management of cardiovascular risk factors in those who undergo amputation and have diabetes. A recent study in the Canadian population reported that predictors of prolonged hospital stay included cardiovascular risk factors, such as diabetes, hypertension, ischemic heart disease, congestive heart failure or hyperlipidemia [42]. …”
Section: Discussionmentioning
confidence: 99%
“…Age-unadjusted rates are not ideal because they do not allow comparison with the rates from other countries or rates across different years that have different age compositions. 13,14 Recently, Kayssi et al 15 reported on LLAs in Canada from 2006 to…”
mentioning
confidence: 99%
“…Vascular surgery persons with amputations, who generally have advanced peripheral arterial disease that necessitates a longer postoperative length of stay in hospital, may require less time at an inpatient rehabilitation facility secondary to initiation of rehabilitation before discharge from hospital. Indeed, we have reported previously that vascular surgery persons with amputations have a longer acute inpatient hospital stay compared with other persons with amputations [3,18]. Unfortunately, we are unable to further explain this postamputation rehabilitation trend with the current dataset.…”
Section: Discussionmentioning
confidence: 56%
“…Although great strides have been made in the medical treatment of the cardiovascular risk factors for amputation, almost 1 in 190 Americans currently is living with the loss of a limb, and that number may double by 2050 [2]. The overall incidence and prevalence of lower extremity amputations is not known, but we have previously shown that 81% of nontraumatic amputations in Canada were carried out as the result of diabetic complications [3].…”
Section: Introductionmentioning
confidence: 99%